Study and Determination of Aryl Hydrocarbon Receptor with Some Trace Elements in Fuel Filling Station Workers - Twaij, Bassem Abd Al-Raheem; Mashkour, Muthana Salam; Al-Hakeim, Hussein Kadhem (Journal of Petroleum Research and Studies, 2020)
PollutiOn is the intrOduction Of contaminantsʹ intO the natural envirOnment that cause adverseʹ change. Gasoline is a toxic and highly flammable liquid consists of various types of aliphatic hydrocarbons, olefins, benzenes and aromatic hydrocarbons including toluene, xylene and a large number of volatile compounds in addition to tetraethyl lead. Gasoline consists of different types of aliphatic hydrocarbons, aryl compounds and some trace elements. Trace elements are several important roles in human bodies, some are essential for enzymes reactions where they attract and facilitate conversion of substrate molecules to specific end products. Aryl hydrocarbon receptor (AHR) is a receptor involved in the regulation of biological responses to planar aromatic hydrocarbons. The aim of the present study is to compare the serum AHR level in the fuel station workers (FSW) with the non-workers as a control group. The other aim is to find out a possible correlation between AHR with trace elements. Sixty male FSW and 30 controls, from ten fuel stations at Al-Najaf City-Iraq, were participated in the present study. The AHR level in serum was measured using ELISA technique. Determine the following metal ions Zn2+, Cu2+, Fe3+, Mg2+, Na+ and K+ level in filling station workers (FSW) and control group were measured spectrophotometrically by using ready for use kits. Serum Pb level was carried out using Atomic absorption spectroscopy. The results serum concentration of AHR in FSW group revealed a significant increase (p<0.001) as compared with the control group. No significant difference was noticed in AHR as compered in exposure ≥12years with exposure <12years in FWS. Smoking has no significant correlation with other parameters. Correlation study indicated a correlation between AHR and Age. Serum concentration of Cu2+, Zn2+, K+ and Pb in FSW group revealed a significant increase (p<0.001) as compared with the control group. While Fe3+, Na+ and Mg2+ in FSW group revealed a significant decrease (p<0.001) as compared with the control group. Correlation study indicated a significant negative correlation between serum Pb and AHR while other trace elements showed no significant correlation with AHR in FSW group. There is a significant negative correlation between serum Cu2+ with age while there is significant increase correlation between Zn2+, Mg2+ and Pb with age in FWS group. Conclusion of study is The role of increase AHR on the health in FSW group, attention to use safety gloves and face mask is recommended for FSW and a long follow-up to the studied group is necessary to explore the prognosis of increase AHR in FSW.